PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN IPS DI KELAS V SEKOLAH DASAR NEGERI 008 TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR TAHUN AJARAN 2015/2016 - Yusmita '; Gusnardi '; RM. Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: IPS education emphasizes providing direct experience and todevelop the competence that the students were able to explore and understand thenature of social processes around scientifically. In addition to quality education can notbe separated from the role of the teacher as facilitator and motivator. a teacher will beeasier to accomplish the desired objectives, if a teacher uses media or tools in theprocess of teaching and learning activities IPS "the teacher as a facilitator should beable to cultivate sources and media useful learning as well as to support theachievement of learning objectives and learning process, and includes sources,textbooks, magazines or newspapers. Media is a tool that impart or disseminate ideas,ideas and opinions that can be presented to the recipients ditujui. Learning Outcomesnamely the ability of the students after receiving the result of the ability to learn. Thelearning result is output achieved thanks to the learning process. The purpose of thisresearch to improve learning outcomes IPS Grade Elementary School V.A 008 megabay, Tanah Putih, Rokan Hilir Aajaran Year 2015/2016 by using media images. Placeof research conducted in SD 008 Mega Gulf Kayu Putih subdistrict. The samples usedwere students of class V.A numbered 20 people. Techniques used in data collection byusing observation sheet student, teacher observation sheet and booklet. Techniquesused to analyze the data of student learning outcomes and engineering activities ofteachers and students. From the analysis done shows that the image method canimprove student learning outcomes SD 008 Mega Gulf Kayu Putih subdistrict RokanHilir.Keywords: Media Images and Learning Outcomes